The big R-book : from data science to learning machines for the professional - De Brouwer, Philippe J. S. (Wiley, 2020)
"This book provides an overall introduction to R with a focus on tools and methods commonly used in Data Science, with an emphasis on practice and business use. The intention is to provide a practical guide for non-experts with a focus on business users. The author covers a wide range of topics in a single book: databases, statistical machine learning, data wrangling, data visualization, and reporting such results. The book includes seven parts. Part 1 is an Introduction, Part 2 provides an overview of R and elements of statistics. Part 3 revolves around data, while Part 4 focuses on data wrangling. Next, Part 5 focuses on exploring data. Modelling is covered in Part 6, while Part 7 covers reports. Finally, Part 7 contains appendices. The topics covered are all important for someone with a science/math background that is looking to quickly learn several practical technologies to enter or transition to the growing field of data science"--